Kreativitas Guru dalam Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Ari Susetiyo; Novida Aprilina Nisa Fitri (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
The ongoing Covid pandemic has paralyzed all sectors, including the education sector, and many people have limitations, including children. Education gave to the maximum in schools. To reduce the existing phenomenon, namely Covid-19, Circular Letter number 4 is enacted, which contains the implementation of learning from home. With the restrictions of distance learning activities carried out at home, the teacher needs to make a design, and distance learning feels interesting and always requires creativity.Therefore, the writer is interested in doing this research. The method in this research is qualitative and is library research or literature study. In describing the creativity of educators in the application of distance learning, the ways are reading, taking notes, and drawing according to the subject matter. The results of this study reveal that the implementation of distance learning has a connection with the Covid-19 pandemic, for educators provide education about Covid-19, namely the dangers and how to prevent it by using hand sanitizers, masks, and other protocol equipment. Guardian accompanies students doing exercise, photos, and videos of their children when carrying out learning activities. As a form of the report.